Client Satisfaction with Services Provided at Integrated Counselling and Testing Centre in a Rural Hospital, Panvel, Maharashtra, India - Sherlin Sam; Nisha Relwani; Prasad Waigankar (Indian Association of Preventive and Social Medicine, 2022)
Introduction : HIV is a global pandemic and has been a serious concern for public health among individuals and communities. Measuring client satisfaction can help the country to carry out an evaluation of the health service system as well as, clients can develop a long-lasting relationship with the service provider. Objectives: 1) To assess the client satisfaction by the services provided at the Integrated Counselling and Testing Centre at the Rural Hospital, Panvel. 2) To provide recommendations to improve the services provided at the Integrated Counselling and Testing Centre. Method: A descriptive, crosssectional, facility-based study was conducted in an Integrated Counselling and Testing Centre (ICTC) at a Rural Hospital, Panvel using simple random sampling technique. Exit interviews were conducted for three hundred clients after the required consent was obtained. Clients were stratified into pregnant and nonpregnant females. All clients above 18 years were included in the study however, clients not giving consent or severely ill were excluded. The data was analyzed using Microsoft Excel, and Epi Info Version 7.2. Results: Among 300 clients, 66% (198) of the clients belonged to the age group of 18-28 years and 54.3% (163) were literate. The study found that nearly74% (222) of the clients were referred and about 71.7% (215) clients were unsatisfied with the ICTC services. Conclusion: Majority of the clients were unsatisfied with the services provided at ICTC. Literate clients were more unsatisfied as compared to illiterate clients.It is further recommended that the counsellors at ICTCs should spend more time with the clients and tere should be a mandatory requirement of female counsellors.